Como influye el uso prolongado de dispositivos móviles en la incidencia de queratoconjuntivitis seca, en pacientes de 20 a 30 años, en Óptica Luque, Ciudad de Ambato, periodo mayo-septiembre 2019 - Chimbo Luque, Juan David (2019)
Keratoconjunctivitis sicca is a chronic reaction of the conjunctiva and cornea of both eyes due to a tear film insufficient. Its symptoms are itching, burning, irritation, and photophobia, the research aimed to Determine if long-term use of mobile devices influences the incidence of keratoconjunctivitis sicca in patients 20 to 30 years, in Optical Luque, a City of Ambato, the period may-September 2019, we worked with a methodology that is qualitative - quantitative (Mixed), the population and sample of worked was 98 people men and women who attend Optical Luque, the results found were that keratoconjunctivitis sicca is more prevalent in the male sex, in age ranges of 20 to 25 years, the most frequent symptom is ocular dryness, 98% of patients have no idea about which is the keratoconjunctivitis sicca, the patients think that it can decrease the incidence of this disease using moderately mobile devices. We used the Schirmer's I test, which allowed to observe the degree of keratoconjunctivitis sicca, which presented the patients being of severity means in the male sex, predominantly in people aged 20 to 25 years, the most common symptom was ocular dryness, at the end, designed a prevention guide that will serve for both optometrists and patients, in conclusion we can assure that there is lack of awareness of the excessive use of cell related to the visual health in the population.